ЎЗБЕКИСТОН ТАРИХИ ФАНИНИ ЎҚИТИШ АСОСИДА ЎҚУВЧИЛАРНИНГ МИЛЛИЙ ҚАДРИЯТЛАРГА ҚИЗИҚИШЛАРИНИ РИВОЖЛАНТИРИШНИНГ ПЕДАГОГИК ТАЛАБЛАРИ - Хакимжонов, Б. (SCIENCE and SOCIETY, 2020)
The article talks about how to increase students’ activity at the lessons in History of Uzbekistan, develop their interst to national values and use pedagogical software in the educational process.
Keywords: national values; historical heritage; routing; pedagogical process; blitz questions; pedagogical software; demonstration method